Significant influence of different sulfur forms on Sulfur-containing polycyclic aromatic compound formation in high-sulfur coals. (15th January 2023) - Zhao, Qiaojing; Qin, Shenjun; Shen, Wenchao; Sun, Yuzhuang
Graphical abstract: Highlight: Sulfur forms may significantly influence the SPACs formation. High organic-sulfur coal contains more SPACs. Sulfur forms were controlled by peat forming environments. SPACs, sulfur forms and peat forming environments belong to a geological system. Abstract: Sulfur-containing polycyclic aromatic compounds (SPACs) are important compounds found in coal. Previous research suggests that sulfur content is the most important controlling factor for SPAC formation. However, different forms of sulfur occur in coal. To study the influences of different sulfur forms on SPAC-formation mechanisms, six samples collected from the No. 14 coal seam of the Yuzhou Coalfield were identified to be high-pyrite sulfur coal (HPSC). Ten samples collected from the No. 11 coal seam from the Yuzhou Coalfield were identified to be high organic-sulfur coal (HOSC). Four samples collected from the No. 15 coal seam of the Dengfeng Coalfield were identified to be high sulfate-sulfur coal (HSSC). The study of the influences of different sulfur forms on SPAC-formation may better understand SPAC-formation mechanism. The collected samples were investigated using a microscope and organic geochemical methods. The microscopic findings revealed that the three coals have similar random vitrinite reflectance ( Rr ) values and have undergone similar geothermal processes. The geochemical results showed that the SPAC species and their contents in the HPSC, HSSC, and HOSC samples are very different. The HOSC samples of the No. 11 coal seam contained 65 SPACs; however, the HPSC samples of the No. 14 coal seam contained only 25 SPACs, and the HSSC samples of the No. 15 coal seam contained 44 SPACs. The average ratio of total-SPAC/total-PAC ( T -SPAC/ T -PAC) reaches 55.0 wt% in the HOSC samples, whereas the ratio is only 19.3 wt% in the HPSC samples, and 22.6 wt% in the HSSC samples. Coal maturity should not be a factor in the SPAC discrepancy because the three coal seams herein underwent similar geothermal processes. The sulfur forms may explain the apparent discrepancy of SPACs. Compared to the other two types of coal, the contents of pyrite, sulfur, and iron (Fe) are much higher in HPSC, and sulfur prefers to react with Fe to form pyrite, resulting in a lower SPAC content in HPSC and HSSC. The sulfur forms were influenced by the peat/coal-forming environments, which were affected by storm events. Finally, possible comprehensive formation pathways for major SPAC species have been proposed.